Lifestyle characteristics of students who are overweight, obese, or have normal body weight - Matejek, Črtomir (Revija za elementarno izobraževanje, 2025)
This study examines the differences in body composition and lifestyle habits between normal-weight (NW) and overweight/obese (OW&O) university students. A sample of fifty-five students aged 21–25 years completed validated questionnaires (HLPCQ, IPAQ-SF, WHO-5) and underwent body composition analysis using the InBody 270 device. Statistical analyses included independent sample t-tests and Cohen’s d effect sizes. OW&O students had significantly higher scores for body fat, fat-free mass, and skeletal muscle mass. While body composition differences were evident, lifestyle habits did not significantly differ between weight groups. Bias in lifestyle and well-being selfassessment calls for the development of more objective assessment tools and further research.
Keywords: body composition; eating habits; gibalna dejavnost; physical activity; Prehrambene navade; sleeping habits; social balance; socialno ravnovesje; spalne navade; Študenti; Telesna zgradba (človek)